First report of the occurrence of East African cassava mosaic virusUganda (EACMVUG) in Angola - Kumar, P. Lava; Akinbade, S.A.; Dixon, Alfred G.O.; Mahungu, N.M.; Mutunda, M.P.; Kiala, D.; Legg, James P. (Wiley, 2009)
Cassava mosaic disease (CMD) is the major production constraint oncassava (Manihot esculenta) in Angola. Previous reports derived fromsingle samples recorded the presence of African cassava mosaic virus(ACMV) and East African cassava mosaic virus (EACMV) in Angola.Regional CMD monitoring initiatives have predicted the spread intonorthern Angola of EACMV-Uganda (-UG), the unusually virulent(aggressive) recombinant strain associated with the African CMDpandemic (Legg et al., 2006). In view of this threat, an assessment surveywas conducted in north and central Angola in April 2008.Eighteen cassava fields were sampled in Bengo, Cuanza Norte, Malanjeand Uige Provinces. Moderate to severe CMD symptoms were observed inmost fields. Sixty-three of 65 samples obtained from these fields testedpositive in TAS-ELISA using monoclonal antibody SCR 20. PCR wasperformed using primer pairs previously described for the specificidentification of ACMV, EACMV, EACMV-UG, East African cassavamosaic Cameroon virus (EACMCV) and Indian cassava mosaic virus(ICMV) (Ogbe et al., 2003), East African cassava mosaic Malawi virus(EACMMV) (Zhou et al., 1998), East African cassava mosaic Zanzibarvirus (EACMZV) (Were et al., 2004) and South African cassava mosaicvirus (SACMV) in mixed infections. This revealed the occurrence ofACMV, EACMV and EACMV-UG, but not EACMZV, EACMMV,SACMV or ICMV. Single infections of ACMV and EACMV were detectedin 32·3 and 9% of samples, respectively. Mixed infections of ACMV withEACMV, EACMV with EACMV-UG and all three viruses were detectedin 35·3, 1·5 and 16·9% of samples, respectively. ACMV, detected in 84·6%of samples, was the predominant species, followed by EACMV (63%) andEACMV-UG (18·5%). Significantly, EACMV-UG occurred mostfrequently in the northernmost part of the surveyed area (Uige Province)immediately to the south of the Bas Congo region of the DemocraticRepublic of Congo, already known to be affected by the pandemic. Thesefindings significantly broaden the known geographical extent of the CMDpandemic and draw attention to the urgent need for the large-scale deploy-ment of resistant cassava varieties, which have been used to reduce lossesin pandemic-affected regions of East Africa.